2021
DOI: 10.18502/sjms.v16i4.9944
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin on Iron Overload in Rats

Abstract: Background: Iron overload, common in patients with hematological disorders, is a key target in drug development. This study investigated the effects of curcumin on iron overload in rats. Methods: Forty male Wistar rats weighing 139.78 ± 11.95 gm (Mean ± SD) were divided into three equal groups: (i) controls; (ii) iron overload group that received six doses of iron dextran 1000 mg/kg–1 by intraperitoneal injections (i.p.); and (iii) iron overload curcumin group that received six doses of curcumin (1000 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Alizadeh et al conducted an animal study and divided 50 Wistar rats into three groups. Similar to the findings of our study, they found that curcumin significantly reduced the levels of ALT, AST, and antioxidants in the blood ( Özbolat and Yegani, 2021 ). Curcumin also caused a significant decline in liver enzymes and cholesterol levels ( Panahi et al, 2016 ; Rahmani et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…Alizadeh et al conducted an animal study and divided 50 Wistar rats into three groups. Similar to the findings of our study, they found that curcumin significantly reduced the levels of ALT, AST, and antioxidants in the blood ( Özbolat and Yegani, 2021 ). Curcumin also caused a significant decline in liver enzymes and cholesterol levels ( Panahi et al, 2016 ; Rahmani et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%